MAGNETIC-RESONANCE-IMAGING IN THE DIAGNOSIS OF IDIOPATHIC GIANT-CELL GRANULOMATOUS HYPOPHYSITIS - A RARE CAUSE OF HYPERPROLACTINEMIA - (:unkn) unknown (GEORG THIEME VERLAG, 1993)
Idiopathic giant cell granulomatous hypophysitis is a rare disorder of pituitary gland characterised by a chronic inflammatory process. It can also be an extremely rare cause of hyperprolactinaemia. In this paper, we present our experience with two cases of idiopathic giant cell granulomatous hypophysitis manifested by hyperprolactinaemia, and their neuroradiological evaluation including preoperative MRI studies in one of them, and discuss our findings in the light of the literature.
Keywords: GRANULOMATOUS HYPOPHYSITIS; HYPERPROLACTINEMIA; HYPOPITUITARISM